2013
DOI: 10.1186/1475-2840-12-126
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and activin A are independently associated with cardiovascular events and mortality in type 2 diabetes: the prospective Asker and Bærum Cardiovascular Diabetes (ABCD) cohort study

Abstract: BackgroundNovel and robust cardiovascular (CV) markers are needed to improve CV morbidity and mortality risk prediction in type 2 diabetes (T2D). We assessed the long term predictive value of 4 novel CV risk markers for major CV events and mortality.MethodsWe included patients with T2D who had cytokines (interleukin [IL]-6 and activin A [actA]), a maximum stress ECG test (evaluated by the normalization pattern in early recovery phase) and echocardiography (evaluated by a measure of the left ventricular filling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Patients with DM are characterized by a state of chronic inflammation and abnormal activation of the innate immune system . Various inflammatory factors, such as monocyte chemoattractant protein‐1 (MCP‐1), tumor necrotic factor‐ α (TNF‐ α ), and C‐reactive protein (CRP) are upregulated in DM, and may play pivotal roles in the development of CVD in DM patients . Recently, gut microbiota were found to be related to obesity, metabolic endotoxemia, and low‐grade chronic inflammation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with DM are characterized by a state of chronic inflammation and abnormal activation of the innate immune system . Various inflammatory factors, such as monocyte chemoattractant protein‐1 (MCP‐1), tumor necrotic factor‐ α (TNF‐ α ), and C‐reactive protein (CRP) are upregulated in DM, and may play pivotal roles in the development of CVD in DM patients . Recently, gut microbiota were found to be related to obesity, metabolic endotoxemia, and low‐grade chronic inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Various inflammatory factors, such as monocyte chemoattractant protein-1 (MCP-1), tumor necrotic factor-α (TNF-α), and C-reactive protein (CRP) are upregulated in DM, and may play pivotal roles in the development of CVD in DM patients. [13][14][15][16] Recently, gut microbiota were found to be related to obesity, metabolic endotoxemia, and low-grade chronic inflammation. [17][18][19][20] Gut microbiota participate in the energy homeostasis of the host by modulating its capacity to harvest energy from given nutrients and in subsequent fat storage, 17 and can be modulated by dietary fiber, polysaccharides, or high-fat diets.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic vascular complications, including macroangiopathy, microangiopathy and peripheral vascular complications, are the most common diabetic complications in both type 1 [ 1 ] and type 2 [ 2 ] diabetes mellitus and make major contributions to diabetic mortality and morbidity [ 2 ]. Diabetic microvascular disease is a leading cause of blindness, renal failure and nerve damage.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the findings of Herder et al, a recent case‐cohort study population comprising 3865 patients from the ADVANCE study affirmed that IL‐6 is a strong and independent predictor of major CV events and death in patients with T2D who have CHD or risk factors at baseline . Furthermore, in a population with T2D and moderately elevated CV risk, IL‐6 provided prognostic information on CV events and mortality beyond conventional CV risk factors . Interestingly, observing the progression of macrovascular complications among patients with T2D and healthy subjects during a 5‐year follow‐up, Wu et al found that IL‐6 has stronger predictive value in diabetic atherosclerosis development, as compared with non‐diabetic atherosclerosis.…”
Section: Inflammation Biomarkersmentioning
confidence: 68%